A arte musical em duas fontes filosóficas: o juízo estético de Kant e a teoria estética de Rookmaaker - Cardozo, Cláudio Roberto (2019)
During the historical process of definitions of what is pleasant, beautiful, and good artistic expression, we are faced with a moment in history when a response to these questions flourished that had such a great impact on the art evaluation process that for almost three centuries thereafter we lack further studies and analyzes for a better understanding and conceptual application of their claims. I am referring to the Critique of the Faculty of Judgment (1790) by the philosopher Immanuel Kant (1724-1804). Although the study of Kant's aesthetic judgment is already a material enough to answer questions of many theses and dissertations, this paper proposes to present another aesthetic theory that also had influenced dozens of European and American universities of the twentieth century: the theory aesthetics of Hans Rookmaaker (1922-1977). This theory was based on Herman Dooyeweerd's (1894-1977) “Philosophy of the Cosmonomic Idea” which in turn was a philosophical system that was born to dialogue, test, oppose and offer an alternative to Kantian philosophy. Therefore, the interest of this work is: to present in the same study two opposing currents of theorization of artistic appreciation applying them in a panoramic view to the musical art and then anyone can will have a glimpse of how they differ, enrich the philosophical study of arts and raise specific questions which may be the subject of further research and future comparative studies.